Al-Udw an al-Irqi ala Ma`had al-Kuwayt lil-Abhath al-Ilmiyah : atharuhu wa-in`ik as atuhu al-saibiyah dir asah watha`iqiyah - Al-Onaizi Sulaiman A. (Al-Mansoria, Kuwait : Center for Research and Studies on Kuwait, 1997)
PSZJBL